O atendimento educacional especializado (AEE) nas Escolas da Rede Municipal de Teresina, Piauí, no olhar de professores - Andrade, Marília Santana (2015)
The discussion on the inclusion of children with disabilities in the regular school system and the concepts and school practices, among other aspects that address inclusion, are among the themes in greater evidence today as it relates to the integration of people with deficiencies in good standing of their citizens, with rights and duties of social participation and contribution. This paper discusses the inclusion in the educational field as well as its possible implications in the Brazilian educational scenario, but specifically in Piauí, especially when you consider the recent guidelines and recommendations of national and international organizations on the subject. Thus, this study aims to unveil how it is being made to include children in special schools network of public education of Teresina - Piauí. The research methodology referenced in this work is exploratory and descriptive research with qualitative approach and data collection used the semi-structured interview. A general analysis of all answers given by respondents allows us to say that the implementation of the educational inclusion policy is developed to provide guarantees inclusion and integration of students in the school environment